Difference between revisions of "Angle Addition Formulas (Trigonometry)"
m (Formatting) |
|||
Line 1: | Line 1: | ||
− | + | <asy> | |
real a,b,c; | real a,b,c; | ||
a=0.4924; | a=0.4924; | ||
Line 27: | Line 27: | ||
draw(rightanglemark(F,E,A,1)); | draw(rightanglemark(F,E,A,1)); | ||
draw(rightanglemark(C,F,D,1)); | draw(rightanglemark(C,F,D,1)); | ||
− | </asy | + | </asy> |
− | + | We let <math>\angle BAC=\alpha</math>, <math>\angle CAD=\beta</math>, <math>AD=1</math>, <math>E</math> the foot of the altitude from <math>D</math> to <math>AB</math> and <math>F</math> the foot of the altitude from <math>C</math> to <math>DE</math>. | |
− | We let <math>\angle BAC=\alpha</math>, <math>\angle CAD=\beta</math>, <math>E</math> the foot of the altitude from <math>D</math> to <math>AB</math> and <math>F</math> the foot of the altitude from <math>C</math> to <math>DE</math>. | ||
− | == | + | == Sine Angle Addition == |
− | We | + | We have that <math>CD=\sin\beta</math> and <math>AC=\cos\beta</math>. Furthermore, we see that <math>\angle CDF=\angle CAB=\alpha</math>. Thus, we see that <math>FE=BC=AC\sin\alpha=\cos\beta\sin\alpha</math> and <math>DF=CD\cos\alpha=\cos\alpha\sin\beta</math>. Thus, we see that <math>\sin(\alpha+\beta)=DE=DF+FE=\cos\beta\sin\alpha+\sin\beta\cos\alpha</math>, giving<cmath>\sin(\alpha+\beta)=\sin\alpha\cos\beta+\sin\beta\cos\alpha.</cmath> |
− | ===Tangent Angle Addition | + | == Cosine Angle Addition == |
+ | We have that <math>CD=\sin\beta</math> and <math>AC=\cos\beta</math>. Furthermore, we see that <math>\angle CDF=\angle CAB=\alpha</math>. Thus, we see that <math>AB=AC\cos\alpha=\cos\alpha\cos\beta</math> and <math>BE=CF=CD\sin\alpha=\sin\beta\sin\alpha</math>. Thus, we see that <math>\sin(\alpha+\beta)=AE=AB-BE=\cos\beta\cos\alpha-\sin\beta\sin\alpha</math>, giving<cmath>\cos(\alpha+\beta)=\cos\alpha\cos\beta-\sin\beta\sin\alpha.</cmath> | ||
+ | |||
+ | == Tangent Angle Addition == | ||
We have already found <math>AE</math> and <math>DE</math> above; thus we get <math>\tan(\alpha+\beta)=\frac{\sin\alpha\cos\beta+\sin\beta\cos\alpha}{\cos\alpha\cos\beta-\sin\alpha\sin\beta}</math>. Dividing numerator and denominator by <math>\cos\alpha\cos\beta</math>, we get<cmath>\tan(\alpha+\beta)=\frac{\tan\alpha+\tan\beta}{1-\tan\alpha\tan\beta}.</cmath> | We have already found <math>AE</math> and <math>DE</math> above; thus we get <math>\tan(\alpha+\beta)=\frac{\sin\alpha\cos\beta+\sin\beta\cos\alpha}{\cos\alpha\cos\beta-\sin\alpha\sin\beta}</math>. Dividing numerator and denominator by <math>\cos\alpha\cos\beta</math>, we get<cmath>\tan(\alpha+\beta)=\frac{\tan\alpha+\tan\beta}{1-\tan\alpha\tan\beta}.</cmath> | ||
+ | |||
+ | {{stub}} |
Latest revision as of 18:15, 13 February 2025
We let ,
,
,
the foot of the altitude from
to
and
the foot of the altitude from
to
.
Sine Angle Addition
We have that and
. Furthermore, we see that
. Thus, we see that
and
. Thus, we see that
, giving
Cosine Angle Addition
We have that and
. Furthermore, we see that
. Thus, we see that
and
. Thus, we see that
, giving
Tangent Angle Addition
We have already found and
above; thus we get
. Dividing numerator and denominator by
, we get
This article is a stub. Help us out by expanding it.